2021
DOI: 10.14202/vetworld.2021.2031-2040
|View full text |Cite
|
Sign up to set email alerts
|

Biological and molecular characterization of a sheep pathogen isolate of Mannheimia haemolytica and leukotoxin production kinetics

Abstract: Background and Aim: Mannheimia haemolytica (Mha) is a common agent of pneumonia in ruminants globally, causing economic losses by morbidity, mortality, and treatment costs. Infection by Mha is often associated with or promoted by respiratory viral pathogens and environmental conditions. Infections due to Mha have rarely been described in small ruminants. This study reports the biological and molecular characteristics of a new Moroccan Mha isolate from small ruminants presenting typical respiratory symptoms. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…A recent study confirmed the higher sensitivity of goats to M. haemolytica than that of sheep [15]. To assess the conferred immunity in this study, we performed experimental infection only on goats.…”
Section: Challenge Studysupporting
confidence: 69%
See 3 more Smart Citations
“…A recent study confirmed the higher sensitivity of goats to M. haemolytica than that of sheep [15]. To assess the conferred immunity in this study, we performed experimental infection only on goats.…”
Section: Challenge Studysupporting
confidence: 69%
“…Vaccination with M. haemolytica bacterins failed to induce effective protection, probably because this bacterium produces some virulence factors involved in clinical disease and mortality [ 19 ]. The Mha leukotoxin is known to be cytotoxic to ruminant leukocytes and has been the subject of studies on its virulence and immunogenicity in cattle [ 15 , 20 ]. The presence of this protein in the vaccine components may contribute to an increase in its efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mastitis develops in camels and ewes. It has also been isolated from certain wild birds and cattle [4][5][6][7]. In particular, M. haemolytica causes bovine pneumonic pasteurellosis (older name) or mannheimiosis.…”
Section: Introductionmentioning
confidence: 99%